Rheological and sensorial evaluation of yogurt incorporated with red propolis - Santos, Marly Silveira (J Food Sci Technol, 2019)
The aim of the present study was to evaluate the use of red propolis extract, as a natural additive, in yogurt. For this, yogurt was produced with red propolis extract (YRP), to replace the additive chemical potassium sorbate, used in the commercial yogurt (CY). Analysis for apparent viscosity, texture and sensorial acceptance were performed. Apparent viscosity and texture measurements of the samples were similar to the control. Sensory evaluation showed that the samples of YRP reached a mean score of 9 on the hedonic scale, the same score found for CY. Regarding the purchase intention, the samples of YRP showed a positive intention by 64.45% of the consumers, and for CY, 68.89%. For the taste, texture, aroma and consistency, the scores were in the range from 8 to 10, for both samples. It can be concluded that the yogurt incorporated with red propolis presents potential for its commercialization in the Brazilian market.